Adapted physical education: how the character development of students with physical disabilities in Yogyakarta, Indonesia? - Erick Burhaein; Diajeng Tyas Pinru Phytanza; Carla Cristina Vieira Lourenço Lourenço (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this study is to describe the learning system of Adapted Physical Education for students with physical disabilities to develop the character of students with physical disabilities. The methodology used used a descriptive method with a qualitative approach and literature study. The type of data collected comes from secondary data in the form of the results of previous experiences and elaborated sentences which are answers from research subjects conducted by means of interviews. The subjects in this study were 30 Adapted PE teachers in Yogyakarta. The research instruments used interview guides and documentation. The interview instrument had previously been validated for each item through expert judgement by two experts (Gregory) with a validity score of 0.86. Adapted PE teachers use various approaches and strategies in learning for students with physical disabilities in an inclusive manner to strengthen physical and character development. The independent curriculum in Indonesia is closely aligned with inclusive education in character development by publishing the Concept and Guidelines for Strengthening Character Education. Although the use of technology has not yet been implemented, teachers agree on the development of technology in learning that is easily accessible, supports active participation of students, and can be adapted according to the individual needs of students.